Effect of training on anthropometric, physiological and biochemical variables of U-19 volleyball players - Manna, I.; Lal Khanna, G.; Chandra Dhara, P. (Journal of Human Sport & Exercise, 2012)
The effect of training on anthropometric, physiological and biochemical variables of Indian male Under 19 years volleyball players was aimed in the present study. A total of 30 Indian male volleyball players (age range: 16.00-18.99 yr; mean age: 17.7 ± 0.5 yr) regularly playing competitive volleyball volunteered for this study. The training sessions were divided into 2 phases (a) Preparatory Phase (PP, 8 weeks) and (b) Competitive Phase (CP, 4 weeks). The training programme consist of aerobic, anaerobic and skill development, and were completed 4 hrs/day; 5 days/week. Selected variables were measured at zero level (baseline data, BD) and at the end of PP and CP. A significant increase (P<0.05) in anaerobic power, back and grip strength, serum urea and HDL-C; and significant decrease (P<0.05) in body fat, recovery heart rate, hemoglobin, triglyceride and LDL-C were noted after training. No significant change was observed in stature, body mass, LBM, HRmax, VO2max, uric acid and total cholesterol level of the players after the training. This would enable the coaches to assess the current status of an athlete and the degree of training adaptability and provide an opportunity to modify the training schedule accordingly to achieve the desired performance.